2006
DOI: 10.1631/jzus.2006.b0028
|View full text |Cite
|
Sign up to set email alerts
|

Promoter trapping in Magnaporthe grisea

Abstract: Application of promoter trapping based on transformation in Magnaporthe grisea is reported in this paper. Two promoter-trapping vectors, designated as pCBGFP and pEGFPHPH, were constructed and transformed into protoplasts of M. grisea. A library of 1077 transformants resistant to hygromycin B was generated. Of which, 448 transformants were found to express eGFP gene in different structures of M. grisea. Three transformants grew slowly, 5 transformants decreased in conidiation and 7 transformants reduced in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Hence, it can be confirmed that the brittleness of boundaries is more relevant to the precipitation of carbonitride than the concentration of Cu in the subscale layer [16]. Figure 13 shows that original control range of N for this high strength weathering steel varies from 0.01% to 0.02%, sometimes even to 0.03%.…”
Section: Net Crack Defect Profile Of High Strength Weathering Steelmentioning
confidence: 73%
“…Hence, it can be confirmed that the brittleness of boundaries is more relevant to the precipitation of carbonitride than the concentration of Cu in the subscale layer [16]. Figure 13 shows that original control range of N for this high strength weathering steel varies from 0.01% to 0.02%, sometimes even to 0.03%.…”
Section: Net Crack Defect Profile Of High Strength Weathering Steelmentioning
confidence: 73%
“…This method has been used to identify tissue specific and temporally regulated genes and promoters in Arabidopsis thaliana [7,27,17]. Xiao-hong and co-workers [9] used two promoter-trapping vectors pCBGFP and pEGFPHPH, to transform protoplasts of Magnaporthe grisea and established that the promoter trapping technique can be used as a tool for functional genomics analysis. Groover and co-workers [8] reported the use of gene and enhancer trap vectors (cGT-1 and cET-1 respectively) carrying the β-glucuronidase (GUS) reporter gene into the poplar genome via Agro bacterium tumefaciens transformation to identify a new class of vascular-expressed gene tagged by enhancer trap line cET-1-pop1-145.…”
Section: Gene Trapping In Usementioning
confidence: 99%